From Biodiversity to Musketry: Detection of Plant Diversity in Pre-Industrial Peloponnese during the Flora Graeca Expedition - C Chimona; Papadopoulou, S; F Kolyva; Mina, M.; S Rhizopoulou (Life, 2022)
As the interest in natural, sustainable ecosystems arises in many fields, wild plant diversity is reconsidered. The present study is based on extant literature evidence from the journey of John Sibthorp (Professor of Botany, Oxford University) to Peloponnese (Greece) in pre-industrial time. In the year 1795, Peloponnese was a botanically unknown region, very dangerous for travellers and under civil unrest, in conjuncture with a pre-rebellion period. Our study reveals approximately 200 wild plant taxa that were collected from Peloponnese localities in 1795, transported to Oxford University (UK), and quoted in the magnificent edition Flora Graeca Sibthorpiana of the 19th century. Moreover, these plants currently constitute a living collection in Peloponnese, confirmed according to updated data on the vascular Flora of Greece. The presented lists constitute a source of information for plant biologists, linking the past to the present, shedding light on the study of adaptive traits of wild Mediterranean plants and revealing the temporal dimension of natural history. Nowadays, increasing and thorough understanding of the considered plants’ functionality to abiotic and biotic environmental stimuli provides a new framework of sustainability and management options.